Overview of current research on traditional Chinese medicine in skin disease treatment: a bibliometric analysis from 2014 to 2024 - Lin Li; Lanfang Zhang; Yuan Li; Yuan Cai; Xue Wen; Chenjie Zheng; Chuyan Wu; Yunlei Bao; Feng Jiang; Nana Sun; Ni Zeng (Pharmaceutical Biology)
Context Recent research has revealed significant advancements in the field of traditional Chinese medicine (TCM) for skin diseases. However, there is a lack of visualization analysis within this research domain.Objective To analyze the research directions and advancements in TCM research in skin diseases.Materials and methods Publications related to TCM in skin diseases from 2014 to 2024 were searched on the Web of Science Core Collection (WoSCC), VOSviewer, CiteSpace, and the R package “bibliometrix” were employed to visualize and analyze the retrieved data.Results The study included 527 articles published in 25 countries. The number of publications consistently increased from 2014 to 2024. The Guangzhou University of Chinese Medicine was the most noteworthy institution in this field. Among the journals in this domain, the Journal of Ethnopharmacology was the most popular, and most frequently co-cited journal. Chuanjian Lu published the most papers and Yin-Ku Lin was the most frequently co-cited author. Among keywords, “psoriasis” appeared the most frequently. Additionally, several emerging research hotspots were identified, indicating the transition from traditional Chinese therapies to investigations of the molecular interactions and network pharmacology of Chinese herbs in treatment of skin diseases over the past decade.Discussion and conclusion This visualization analysis summarizes the research directions and advancements in TCM research on skin diseases. It presents a comprehensive examination of the latest research frontiers and trends and serves as a valuable reference for scholars engaged in the study of TCM research.